Case Report: Heterogeneity of Resistance Mechanisms in Different Lesions Co-Mediate Acquired Resistance to First-Line Icotinib in EGFR Mutant Non-Small Cell Lung Cancer - Liu, Zhicong; Dong, Hui; Chen, Wenyan; Wang, Bin; Ji, Dongxiang; Zhang, Wei; Shi, Xuefei; Feng, Xueren (Frontiers in Medicine, 2022)
Epidermal growth factor receptor (EGFR)-activating mutations are major oncogenic mechanisms in non-small cell lung cancer (NSCLC). Most patients with NSCLC with EGFR mutations benefit from targeted therapy with EGFR- tyrosine kinase inhibitors (TKIs). One of the main limitations of targeted therapy is that the tumor response is not durable, with the inevitable development of drug resistance. Previous studies demonstrated that the potential resistance mechanisms are diverse, including the presence of EGFR T790M, MET amplification, mesenchymal transformation, and anaplastic lymphoma kinase (ALK) rearrangement. The patient in our report was diagnosed with stage IA lung adenocarcinoma harboring the EGFR L858R mutation and underwent radical surgery. The patient received icotinib for 12 months after recurrence. Subsequent molecular analysis of the left pleural effusion indicated that LCLAT1-ALK fusion might be an underlying mechanism contributing to the acquired resistance to icotinib. Ensartinib was prescribed, but the lesion in the right lung continued to progress. Hence, re-biopsy and molecular analysis of lesions in the right lung were performed to solve this problem. In contrast to the left pleural effusion, EGFR exon 20 T790M might have mediated the acquired resistance in lesions in the right lung of this patient. The combination of osimertinib and ensartinib has achieved a rapid partial response until now. The complexity and heterogeneity in our case may provide new insights into the resistance mechanisms of targeted therapy.